Assessing Five Genre Writing Task-Based Practice On the Second-Year Diploma 3 IT Studentsâ IELTS Writing Test-like Essay - Marsaulina, Rumondang Miranda (Proceeding of International Conference on Teacher Training and Education, 2016)
This paper assessed the results of five genre writing task-based practice in the second-year Diploma 3 ITstudentsâ skills for writing an IELTS writing test-like essay. The problem of the study was to explore howthe five genre writing practice impacted the studentsâ ability to discuss their opinion academically. Theparticular objective of this study was to inquire if the task-based learning enabled the students to ponderideas and express opinions into well-defined, coherent and written explanations in compliance with goodIELTS essay standard. The study was conducted in a quantitative method in which the studentsâ grades of aÂ class test given after completing the tasks were analyzed based on the IELTS Task 2 Writing BandDescriptors and modified IELTS Reading Task Band Score Converter. The results showed the task-basedlearning method instructing the students to yield five basic essay genres from Narrative to Argumentativeneeded to be only focused on Argumentative genre writing task practice if the learning objective was toequip the students to produce an IELTS typical essay in good quality, for the studentsâ essay writing gradesrevealed an unsatisfactory prediction band score, only 4.5 from a scale of 0 to 9. In particular, they shouldtake more intensive drills in organizing unbiased but persuasive explanations, providing supporting examplesÂ for their personal views, picking proper transition markers for the text coherence and being aware ofÂ fragment and run-on sentences, Subject and Verb disagreement, Use of Tenses and Redundancy.